CSR of portuguese companies listed on Euronext Lisbon: a multivariate analysis - Afonso, Sandra Cristina (2013)
The purpose of this paper is to present a cluster analysis applied to group companies by their social performance and to compare the results. The results indicate that companies with better social performance are not the ones with better economic performance, and it suggests that the middle path might provide a good relation CSR-Economic performance, as a basis to sustainable development. The study focused on 19 quoted Portuguese companies and the analysis covered a period of five years, between 2005 and 2009. The results indicated that three clusters were classified in CSR Low (3 companies), CSR Medium (12 companies) and CSR High (4 companies). According to the cross validated classification based on discriminant analysis, the results reveal that 94.7% of the cases were classified correctly.